UTILIZATION OF RICE AND KENCUR (KAEMPFERIA GALANGA) IN IMPROVING IMMUNITY IN THE COVID-19 PANDEMIC - Fauji, Ade; Herawati, Debi; Seliah, Seliah (Nindikayla Institute, 2024)
Rice is a staple food for most Indonesians. Rice consumption in Indonesia is increasing every year along with the increasing population of Indonesia. Rice is a food source of energy that has a high carbohydrate content but low protein. Rice has been known to have a high glycemic index, resulting in increasing glucose levels in the blood. Kencur (Kaempferian shipyard) is a tropical plant that contains chemical substances and compounds. Among them are starch, mineral, sineol, methyl canyl acid, penta dekaan, sinamic acid, ethyl ester, borneol, kamfen, paraeumarin, anisic acid, alkaloid, and gom. Useful for health to be used as antibacterial, antioxidant and herbal medicinal ingredients or made traditional herbal drinks and as a spice in cooking. Rhizome kencur has a soft aroma and a unique spicy taste. The aroma of the rhizome is caused by the chemical components derived from essential oils. As an herbal remedy, kencur has cough medicine, appetite enhancer, boosting the immune system